Taiwan [videorecording] more than an island. (Government Information Office, 2005)
In the mid 16th century, the beauty of Taiwan enchanted the Portuguese, who named it Ilha Formosa, or beautiful island. In the second half of the 20th century, this self sufficient agrarian island transformed into a vidorous and advanced economy. With insightful prose and lavish photographs, this CD-ROM presents the story of Taiwan in various aspects. Knowing Taiwan has never been easier.